2022
DOI: 10.31729/jnma.6417
|View full text |Cite
|
Sign up to set email alerts
|

Sunscreen Use among Medical Undergraduate Students in a Medical College: A Descriptive Cross-sectional Study

Abstract: Introduction: Unprotected sun exposure could cause tanning, burning, hyperpigmentation, skin aging, and even skin cancer. Regular sunscreen use is a safeguard and a primary preventive strategy against sunlight-related damages. This study aims to find out the prevalence of sunscreen use among medical undergraduate students of a medical college of Eastern Nepal. Methods: A descriptive cross-sectional study was conducted among the current medical undergraduate students of 2 medical colleges in Nepal on sunscreen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Other studies also reported similar findings among medical students. 9,7,11 They lacked knowledge of application, mainly in the areas of season, place, skin color, and body parts to be applied and its frequency of application. Compared to ours, the students from Indonesia had better knowledge regarding these parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies also reported similar findings among medical students. 9,7,11 They lacked knowledge of application, mainly in the areas of season, place, skin color, and body parts to be applied and its frequency of application. Compared to ours, the students from Indonesia had better knowledge regarding these parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Such gender disparities in awareness and usage of sunscreen among medical students and the general population were also found in other studies. 7,9,12 These gender differences may have resulted from cultural norms and societal expectations for females to have fair skin, which led them to prevent suntan. 13 On top of that, females are cosmetically more aware and concerned with their outlook than their counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation